Chronic periodontitis as a risk factor for atherosclerotic cardiovascular disease: Periodontitis kronis sebagai faktor risiko penyakit kardiovascular aterosklerosis - tira nurfaizah; A. Mardiana Adam (Makassar Dental Journal, 2023)
Recent studies implicate exposure to systemic conditions involving chronic inflammation, including chronic periodontitis, in the etiology of atherosclerosis. Periodontal disease is a very common disorder affecting the global population. This study briefly describes chronic periodontitis as a risk factor for cardiovascular disease in atherosclerosis based on existing literature. Ten articles from various electronic databases and manual searches were reviewed that updated the epidemiologic evidence of a signi-ficant association between periodontitis and arterosclerosis, mechanistic relationships and the impact of periodontal therapy on cardiovascular. The review also focused on the potential risks and complications of periodontal therapy on antithrombotic therapy. It is concluded that in both diseases multiple systemic inflammatory mechanisms including elevated levels of inflam-matory mediators, lipids, and hemostatic and thrombotic factors occur, thus there appears to be an association between chronic periodontitis on the one hand and atherosclerotic disease on the other.